(untitled) (Global Journal of Human-Social Science, 2020)
The readymade garments workers in Bangladesh are the most important persons in the economy of Bangladesh. Without their contribution, we have not got the status of a middleincome country. There is a distinct similarity between the garment’s workers and slavery in terms of the long work hours, wage gap, and curbing human rights. This research is focused on the relation between power and labor in the garment factory. So, this paper is based on the theory of ’Coloniality of Power’ by Anibal Quijano (2000). It is investigating how the labourers have become modern ’slaves’, how they are being treated, and how their flesh and blood are used to bear the practice of colonialism. This paper concludes with some recommendations for stopping this practice.